IMPLEMENTASI TAMPILAN WEBSITE PADA SEKOLAH MENENGAH ATAS NEGERI 1 KAWALI DENGAN MENGGUNAKAN METODE KANSEI - Izulhaq, Ilham; Mulyana, Dadan; Sidiq, Maulana (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
This study uses the Kansei Engineering method to design the website interface design. It uses the Kansei Engineering Type 1 methodology to generate ideas for website interface design. The Kansei word list used is 10 words related to website interface design. A total of five specimens are used for website interface design. This study involved 50 participants, consisting of 48 high school students in Grade X and 2 teachers in computer science, who produced a new design product in the form of the "Innovative" emotion concept.